184k views
5 votes
How do I slove this eqaution, and whats the answer?
-3(n+6)+10=-9

1 Answer

1 vote

Answer:


n = (1)/(3)

Explanation:

  1. Apply the distributed property, so it now looks like this: -3n + -18 + 10 = -9
  2. Combine like terms: -3n + -8 = -9
  3. Simplify: -3n - 8 = -9
  4. Add 8 to each side, so it now looks like this: -3n = -1
  5. Divide each side by -3 to cancel out the -3 next to n. It should now look like this: n = 1/3

I hope this helps!

User Sergei Rogovtcev
by
5.7k points